2016
DOI: 10.1039/c5sm02736e
|View full text |Cite
|
Sign up to set email alerts
|

Local coordination and dynamics of a protic ammonium based ionic liquid immobilized in nano-porous silica micro-particles probed by Raman and NMR spectroscopy

Abstract: Room temperature ionic liquids confined in a solid material, for example, nano-porous silica, are particularly propitious for energy related applications. The aim of this study is to probe the molecular interactions established between the protic ionic liquid diethylmethylammonium methanesulfonate (DEMA-OMs) and silica, where the latter consists of nano-porous micro-particles with pores in the size range of 10 nm. The changes in the local coordination and transport properties induced by the nano-confinement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…22 In this contribution we present a new type of ion-conducting gel that builds upon recent results obtained with nanoporous silica micro-particles filled with an ionic liquid, where the silica structure is designed to provide extremely well-connected nanopores, very good mechanical properties, and a high surface area. 20 We here demonstrate by different experimental techniques that the ionic mobility is significantly enhanced by chemical functionalization of the silica surface, and we also present a molecular level explanation based on a flipped-ion effect. By validating these results for two very different ionic liquids, one protic short-chained and one aprotic long-chained, we demonstrate that the positive effect on ionic mobility is of general validity.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…22 In this contribution we present a new type of ion-conducting gel that builds upon recent results obtained with nanoporous silica micro-particles filled with an ionic liquid, where the silica structure is designed to provide extremely well-connected nanopores, very good mechanical properties, and a high surface area. 20 We here demonstrate by different experimental techniques that the ionic mobility is significantly enhanced by chemical functionalization of the silica surface, and we also present a molecular level explanation based on a flipped-ion effect. By validating these results for two very different ionic liquids, one protic short-chained and one aprotic long-chained, we demonstrate that the positive effect on ionic mobility is of general validity.…”
Section: Introductionmentioning
confidence: 61%
“…19 Diffusion NMR experiments have revealed that compared to the previous (sol-gel derived) ionogels, in these gels the mobility loss due to confinement is significantly reduced from 58% to 25% of the bulk value. 20 We have also verified by detailed spectroscopic studies including nuclear magnetic resonance (NMR), Raman and infrared, that the origin of this loss is related to surface interactions established at the ionic liquid/silica interface, i.e. at the pore walls.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations